DEVELOPING ENGLISH SPEAKING MATERIALS BASED ON CONTEXTUAL TEACHING AND LEARNING FOR STUDENTS OF ELECTRICAL ENGINEERING AT SMK SINAR HUSNI MEDAN - Rahmi Rahmadani; Anni Holila Pulungan; Tiarnita Siregar (Universitas Negeri Medan, 2018)
This research aim to design English speaking materials needed for students of electrical engineering study program at SMK Sinar Husni Medan. This study was conducted by using Research and Development (R & D) design through six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product.The subject of this study were students of class X-l2 of electrical engineering study program consisting of 38 students. The instrumentations for collecting the data were questionnaire and interview. After analyzing the data, the writer got the students’ needs. The data were gathered by administering interview to the English teacher and distributing the questionnaire to 38 respondents to get the students’needs. The interview and questionnaire results prove that the students need English reading materials which contain English for electrical engineering study program. Thus, The materials were then developed through Contextual Teaching and Learning approach which implementation by REACT (relating, experiencing, applying, cooperating, and transferring) and developed with their study program and work life situation. The learning materials were developed into 6 units of speaking material. by two experts; English lecturer and English teacher. The average scores are 4,5 or 90% from English Lecturer and 4,4 or 87,6% from English teacher.It means the developing materials categorized as relevant or appropriate for grade X students of electrical engineering study program. Key words: Research and Development (R & D), Speaking materials,Contextual Teaching and Learning, Electrical Engineering Program